A catalogue of software tools for digital scholarly editing - Chiara Martignano (Umanistica Digitale)
In the field of digital philology a large number of software tools has been developed through the years and keeps being developed in order to assist (or substitute) editors in the making of a digital scholarly edition (DSE). The growing number of software tools for scholarly editing has created a need for a dedicated catalogue to help scholars and institutions select current tools that best fit their research purposes. A specialised catalogue would also serve as a valuable resource for studying the historical technological trends and methodologies in digital philology. Creating this catalogue requires careful consideration of both practical and theoretical aspects. This paper evaluates existing tool discovery resources, examines the catalogue’s potential scientific value, and addresses key implementation challenges. A prototype catalogue is then presented, exploring possibilities for its future development.